Terrestrial predatory leeches of the genus Orobdella (Hirudinea: Erpobdelliformes: Orobdellidae) endemic to the Southern Russian Far East: a new species of the genus from Primorsky Krai, Russia - Nakano, Takafumi; Prozorova, Larisa A. (Zootaxa, 2024)
A quadrannulate species, Orobdella ganini sp. nov., is described from the Lazovsky Nature Reserve in Primorsky Krai, the Southern Russian Far East, Russia. Morphological features of O. ghilarovi Nakano & Prozorova, 2019 from the reserve are also provided leading to an amendment of the species diagnosis. Maximum likelihood and Bayesian inference phylogenetic analyses, which were performed using nuclear 18S rRNA, 28S rRNA, and histone H3, and mitochondrial cytochrome c oxidase subunit I, tRNACys, tRNAMet, 12S rRNA, tRNAVal, 16S rRNA, tRNALeu and NADH dehydrogenase subunit 1 markers, show that O. ganini sp. nov., O. ghilarovi and two species endemic to Hokkaido, Japan form a clade, with the new species sister to a lineage composed of the two Japanese species. A partial cytochrome c oxidase subunit I sequence obtained from a cocoon found in the Lazovsky Nature Reserve reveals that Orobdella leeches deposit cocoons somewhat similar to those deposited by terrestrial blood-sucking leeches of Haemadipsidae.